2010
DOI: 10.1258/acb.2010.010025
|View full text |Cite
|
Sign up to set email alerts
|

A review of hyperprolactinaemia and severe mental illness: Are there implications for clinical biochemistry?

Abstract: Hyperprolactinaemia is a common adverse event reported in association with treatments used in schizophrenia and bipolar disorder. Recent data are suggestive that hyperprolactinaemia may have a range of significant short-and long-term clinical consequences. The objective of this review is to examine the causes, frequency and clinical consequences of hyperprolactinaemia in the severely mentally ill (SMI) with a focus on patients taking antipsychotic medications. A Medline search was carried out to identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 88 publications
(199 reference statements)
1
57
0
3
Order By: Relevance
“…PRL within gonadotroph cells are controlled by dopamine, the main hypothalamic inhibitory regulator of PRL release in vivo, this specific actions of PRL within the gonadotroph and the cell signaling interactions that ultimately underlie hyperprolactinemia-induced infertility (27); hyperprolactinemia can occur in physiological and pathological conditions (28) such as psychotic stress, severe mental illness or other causes, and the reproductive dysfunction affecting about one third of infertile women (29).…”
Section: Resultsmentioning
confidence: 99%
“…PRL within gonadotroph cells are controlled by dopamine, the main hypothalamic inhibitory regulator of PRL release in vivo, this specific actions of PRL within the gonadotroph and the cell signaling interactions that ultimately underlie hyperprolactinemia-induced infertility (27); hyperprolactinemia can occur in physiological and pathological conditions (28) such as psychotic stress, severe mental illness or other causes, and the reproductive dysfunction affecting about one third of infertile women (29).…”
Section: Resultsmentioning
confidence: 99%
“…Given these recommendations and given the fact that antipsychotics are often utilized outside their licensed applications, 1 the potential workload for the laboratory from patients treated with antipsychotic drugs is considerable. This is illustrated in a recent report that indicated that 25% of prolactin requests came from psychiatry.…”
Section: Workloadmentioning
confidence: 99%
“…(1) Manufacturers should review their reference intervals for serum prolactin and consider carrying out further studies in line with recommended practice 8 to improve their accuracy; (2) Laboratories should review their quoted reference intervals and consider whether these are appropriate for patients undergoing treatment with antipsychotics; (3) It seems probable that inaccurate reference intervals for serum prolactin will have affected the data reviewed by Bushe et al 1 and the estimates of the prevalence of hyperprolactinaemia in patients treated with antipsychotics and estimates of the prevalence by antipsychotic. Once reliable reference intervals are established, these data should be reviewed.…”
Section: Reference Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactin is a polypeptide hormone originally discovered from the crop glands of pigeons in 1933 (Riddle et al, 1933; Bushe and Pendlebury, 2010), however there was some scepticism that prolactin even existed in humans until the 1970s as human prolactin was considered identical to growth hormone (GH). During the 1970s, the development of radioimmunoassay techniques allowed the isolation of prolactin and its subsequent measurement (Kohen and Wildgust, 2008).…”
Section: Introductionmentioning
confidence: 99%